Community Service and MSME Strengthening Based on Green Economy, Business Digitalization, and Financial Literacy in Supporting Sustainable Poverty Alleviation - Sutrisno; Hizbul Khootimah Az Zaakiyyah; Desi Kristanti (PT. LITERASI SAINS NUSANTARA, 2026)
This study aims to analyze and enrich the literature related to community service in strengthening Micro, Small, and Medium Enterprises (MSMEs) based on the green economy, business digitalization, and financial literacy in supporting sustainable poverty alleviation. The study employs a qualitative approach using a literature review method analyzed descriptively. Data were collected from Google Scholar and various credible websites within the period 1977–2026. Out of 50 identified articles, a rigorous selection process based on relevance, quality, and scientific contribution resulted in 40 articles for further analysis. The findings indicate that community service plays a strategic role in enhancing MSME capacity through an integrated approach combining digitalization, financial literacy, and green economy practices. The integration of these three aspects has been proven to improve business efficiency, the quality of financial decision-making, and environmental sustainability. However, several challenges remain, including low digital literacy, limited access to financing, and insufficient continuous mentoring. Therefore, an integrative, contextual, and sustainable community service model supported by multi-stakeholder collaboration is needed. This study is expected to provide both theoretical and practical contributions to the development of more effective and sustainable MSME empowerment programs.